Efecto de las Actividades Físicos Recreativas en estudiantes con trastorno de déficit de atención e hiperactividad en la Unidad Educativa “Lauro Damerval Ayora” 2023-2024. - Collaguazo Medina, Alexander Paul (2024)
The present work of curricular integration was carried out with the objective of analyzing the impact of physical-recreational activities on the behavior and performance of fifth grade students, parallel A, who suffer from attention deficit hyperactivity disorder (ADHD) at the Lauro Damerval Ayora School during the period 2023-2024. This study was based on a mixed approach, using a correlational and quasi-experimental design. The instruments used included an observation form applied to a sample of 5 students with ADHD, as well as a psycho-pedagogical and ADHD assessment questionnaire addressed to the teacher. The results obtained from the observation sheet served as the basis for the elaboration and execution of the pedagogical proposal focused on various physical-recreational activities, which were integrated into the Physical Education didactic unit plan and put into practice during the classes. A significant improvement in the teaching-learning process of the students was observed, which could be evidenced by reapplying this instrument. Keywords: Attention Deficit Hyperactivity Disorder (ADHD), Physical recreational activities, Pedagogical proposal, Teaching-learning.